2012
DOI: 10.1590/s1516-35982012001000015
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance and efficiency of utilization of the diet components in dairy cows fed castor meal treated with calcium oxide

Abstract: -The effect of replacing of 0; 0.33; 0.67 and 1.0 (kg/kg) of soybean meal (SBM) by undecorticated castor seed meal treated with calcium oxide (CMT -60 g/kg) was evaluated on performance and efficiency of nutrient utilization in dairy cows. Sixteen Holstein and crossbred cows were distributed in four 4 × 4 latin squares. Animals received concentrated feed at a ratio of 1 kg for 3 kg of milk produced, in the natural matter. The diets had the same amount of nitrogen (150.4 g crude protein/kg DM), containing 325.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
1
11
1
2
Order By: Relevance
“…Cobianchi et al (2012), who worked with different levels of inclusion of castor bean meal in lactating cows feed, obtained maximum dry matter intake with the inclusion of 5% in the total diet, different from that found in the present study. This difference may be due to the heterogeneity of castor bean byproducts.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Cobianchi et al (2012), who worked with different levels of inclusion of castor bean meal in lactating cows feed, obtained maximum dry matter intake with the inclusion of 5% in the total diet, different from that found in the present study. This difference may be due to the heterogeneity of castor bean byproducts.…”
Section: Resultscontrasting
confidence: 99%
“…Pina et al (2006) compiled several studies using animals for the production of meat and milk subjected to different feeding management, and recommended microbial efficiency of 120 g CPmic kg TDN -1 as reference for tropical conditions. Results close to that found by Cobianchi et al (2012), which found mean values for microbial efficiency at 126.4g CPmic kg TDN -1 , working with different levels of castor bean in the diet for lactating cows.…”
Section: Resultssupporting
confidence: 86%
“…However, the use of detoxified castor bean meal in place of soybean meal can negatively affect some productivity parameters. Cobianchi et al (2012) observed that the substitution of 0.67 kg/ kg of soybean meal by detoxified castor bean meal with calcium oxide reduced production and milk composition in cows with daily production of 20 kg. In another study, Pompeu et al (2012) found that every 1% replacement of soybean meal by castor bean meal was estimated to decrease average daily weight gain by 0.62 g/day.…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo a trabajos realizados con subproductos de higuerilla sobre la producción de leche en bovinos, se ha encontrado que la harina de higuerilla puede sustituir una tercera parte la torta de soya o incluirse en un 5 % en la dieta total o un consumo máximo de 860 gramos de MS en vacas con una producción entre 20 y 25 litros 14,17 , aunque se ha reportado que el nivel óptimo económico de sustitución es del 100 % en vacas en el primer tercio de lactancia 55 . Lo cual es consistente con lo encontrado con este trabajo, puesto que la torta de higuerilla desintoxicada con Ca(OH) 2 , puede sustituir completamente la torta de soya, siempre y cuando se incluya en un nivel del 10 % en un suplemento alimenticio comercial, equivalente al 3,2 % de inclusión de MS de la dieta total o un consumo máximo por vaca de 800 gramos.…”
Section: Experimentounclassified
“…En estudios realizados con subproductos de higuerilla en ganado lechero, se ha encontrado que la harina de higuerilla desintoxicada puede reemplazar hasta un 33 % la harina de soya o incluirse máximo en un 15 % en un suplemento sin afectar la producción de leche en vacas Holstein, cuya base forrajera era ensilaje de maíz 14 . Mientras que en vacas cruzadas (Holstein x Cebú), este subproducto puede sustituir el 100 % la torta de soya e incluirse en un 22,3 % en un suplemento sin afectar la producción y calidad de la leche en vacas pastoreando B. decumbens 43 …”
Section: Introductionunclassified